Ödön von Horváth, Himmelwärts / Mit dem Kopf durch die Wand, Band 2 - Streitler-Kastberger, Nicole (17770696-75f1-4578-889a-eff8c227c542, 2020)
This new volume makes two little-known dramas by Ödön von Horváth, Heavenwards and Head through the Wall accessible to scholars for the first time. Written in the years 1934/35, they document Horváth's struggle to find an adequate response to Nazi Germany and to re-position himself as an author and dramatist.Volume 1: https://e-book.fwf.ac.at/o:1418Volume 2: https://e-book.fwf.ac.at/o:1419